Detection of Cancer Nodules Using Transforms (International Journal of Engineering and Computer Science, 2018)
In this paper, a computer aided detection of cancer nodules in Computed Tomography (CT) images of lungs using radon transform, ridgelet transform and Curvelet transform is proposed. The lung lobes are segmented from the CT images using morphological operations. The transforms are applied to the segmented lung lobes. From the transformed image, the presence of nodules in the lung lobes can be detected and located. The proposed detection method gives an accuracy of 98.5% with a sensitivity of 97.39% and specificity of 100%.